THE COMPARISON ANALYSIS OF WORK RELATED ATTITUDE BETWEEN PERMANENT EMPLOYEE’S AND TEMPORARY EMPLOYEE’S IN BANK SULUT - Handayani, Tri (Universitas Sam Ratulangi, 2015)
Human resources is one of the important aspect in the management. Thereover recruitment must be accommodate by management, in order to achieve the company’s goal. Employees behavior at work will influence employee’s output. Currently, the company is not only recruit a permanent employees but also hire a temporary employee. The objectives of this research to measure if there are significant differences in work attitudes between permanent employees and temporary employee in the Bank Sulut. This research is a comparative study that uses a comparison method. Results of the study shows that there is no significant difference in the work attitude of job satisfaction and organizational commitment between permanent employees and temporary employees Furthermore, other results show that there are significant differences in work attitudes of employee engagement and organization perceived between permanent employees and temporary employee in Bank Sulut. Bank Sulut management should maintain this current condition, but still need to improve the service, quality of its employees, both permanent employees and temporary employees. Keywords: permanent employees, temporary employees, attitude to work